The Effect of Motivation and Work Discipline on the Performance of Private Vocational Teachers in Seberang Ulu II District, Palembang City - Lilis Lilis; Bukman Lian; Nurlina Nurlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The quality of education is currently the main consideration in this study. The quality of education is generally associated with the highest level of performance indicated by the ability of students to achieve high scores in exams and their ability to learn and do assignments. The importance of the quality of education is due to the fact that this quality also greatly affects the development of the country. Therefore, almost every country in the world is trying to improve the quality of education as a means to improve the standard of living of the general public, good and quality education is created from the performance of a quality teacher as well. Therefore, this study aims to determine the effect of motivation and work discipline on teacher performance. This study uses a quantitative method, through a questionnaire distribution process involving 4 private vocational schools across Ulu II, Palembang City with a total of 93 teachers, the results of the study indicate that motivation and work discipline simultaneously have a significant effect on teacher performance. The conclusion of this study recommends the importance of motivation and work discipline on teacher performance, it is recommended that schools carry out teacher development programs that focus on increasing motivation and discipline.